Capt. C.G. Bowman Selected Skipper of 'Golden Bear' - Vallejo Times-Chronicle (Vallejo Times-Chronicle)
The board of governors of the California Maritime Academy has appointed Capt. Carl G. Bowman, USCG, chief of staff, Twelfth Coast Guard District in San Francisco, as commanding officer of the training ship, Golden Bear.